2003
DOI: 10.1074/jbc.m209640200
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2 Degradation Mediated by the Co-chaperone Protein CHIP

Abstract: ErbB2 overexpression contributes to the evolution of a substantial group of human cancers and signifies a poor clinical prognosis. Thus, down-regulation of ErbB2 signaling has emerged as a new anti-cancer strategy. Ubiquitinylation, mediated by the Cbl family of ubiquitin ligases, has emerged as a physiological mechanism of ErbB receptor down-regulation, and this mechanism appears to contribute to ErbB2 down-regulation induced by therapeutic anti-ErbB2 antibodies. Hsp90 inhibitory ansamycin antibiotics such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
190
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(200 citation statements)
references
References 39 publications
8
190
1
1
Order By: Relevance
“…(3) Several groups have reported that Runx2 protein stability is controlled through a ubiquitinproteasome-mediated protein degradation mechanism by Smurf1, (4) Schnurr-3 (Shn3)/WWP1, (5) and CHIP. (6) CHIP/STUB1 is a cochaperone protein identified through its interaction with Hsc/Hsp70, (7) and promotes the ubiquitination and degradation of chaperone-bound proteins, including receptor tyrosine kinase ErbB2, glucocorticoid receptor, (8) SCR-3, (9) Smads, and the mis-folded cystic fibrosis transmembrane conductance regulator protein. (10) Previously, we found that CHIP negatively regulates osteoblast differentiation by mediating degradation of Runx2.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Several groups have reported that Runx2 protein stability is controlled through a ubiquitinproteasome-mediated protein degradation mechanism by Smurf1, (4) Schnurr-3 (Shn3)/WWP1, (5) and CHIP. (6) CHIP/STUB1 is a cochaperone protein identified through its interaction with Hsc/Hsp70, (7) and promotes the ubiquitination and degradation of chaperone-bound proteins, including receptor tyrosine kinase ErbB2, glucocorticoid receptor, (8) SCR-3, (9) Smads, and the mis-folded cystic fibrosis transmembrane conductance regulator protein. (10) Previously, we found that CHIP negatively regulates osteoblast differentiation by mediating degradation of Runx2.…”
Section: Introductionmentioning
confidence: 99%
“…In each case, treatment with GA or 17-AAG results in loss of chaperone function that leads to ubiquitination and degradation by the proteasome [5]. The ubiquitin ligase called Chip is thought to play a role in this process since it stimulates degradation of Hsp90 client proteins in the presence of GA [6][7][8][9]. However, GA can still promote degradation of a client kinase, ErbB2, even in Chip −/− fibroblasts, albeit with reduced kinetics [6].…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that free ubiquitin becomes sequestered when the proteasome is inhibited with lactacystin. However, inhibition of proteasomal activity leads to an accumulation of ubiquitinylated ErbB2 (Zhou et al, 2003;our unpublished data), and more importantly ErbB2 was found still to become ubiquitinylated in cells treated with lactacystin and GA (Mimnaugh et al, 1996; our unpublished data).…”
Section: Proteasomal Activity Is Needed For Cleavage Of Erbb2mentioning
confidence: 99%